Enhanced prediction of renal function decline by replacing waist circumference with “A Body Shape Index (ABSI)” in diagnosing metabolic syndrome: a retrospective cohort study in Japan - Nagayama, Daiji; Fujishiro, Kentaro; Tsuda, Shinichi; Watanabe, Yasuhiro; Yamaguchi, Takashi; Suzuki, Kenji; Saiki, Atsuhito; Shirai, Kohji (International Journal of Obesity, 2022)
Background Abdominal obesity as a risk factor for diagnosing metabolic syndrome (MetS) is conventionally evaluated using waist circumference (WC), although WC does not necessarily reflect visceral adiposity. Objective To examine whether replacing WC with “A Body Shape Index (ABSI)”, an abdominal obesity index calculated by dividing WC by an allometric regression of weight and height, in MetS diagnosis is useful for predicting renal function decline. Subjects/Methods In total, 5438 Japanese urban residents (median age 48 years) who participated in a public health screening program for 4 consecutive years were enrolled. Systemic arterial stiffness was assessed by cardio-ankle vascular index (CAVI). The predictability of the new-onset renal function decline (eGFR < 60 mL/min/1.73 m 2 ) by replacing high WC with high ABSI (ABSI ≥ 0.080) was examined using three sets of MetS diagnostic criteria: Japanese, IDF and NCEP-ATPIII. Results In Japanese and NCEP-ATPIII criteria, MetS diagnosed using ABSI (ABSI-MetS) was associated with significantly higher age-adjusted CAVI compared to non-MetS, whereas MetS diagnosed using WC (WC-MetS) showed no association. Kaplan–Meier analysis of the rate of new-onset renal function decline over 4 years (total 8.7%) showed remarkable higher rate in subjects with ABSI-MetS than in those without (log-rank test p < 0.001), but almost no difference between subjects with and without WC-MetS ( p = 0.014–0.617). In gender-specific Cox-proportional hazards analyses including age, proteinuria, and treatments of metabolic disorders as confounders, ABSI-MetS (Japanese criteria for both sexes, IDF criteria for men) contributed independently to the new-onset renal function decline. Of these, the contribution of IDF ABSI-MetS disappeared after adjustment by high CAVI in the subsequent analysis. Conclusion In this study, replacing WC with ABSI in MetS diagnostic criteria more efficiently predicted subjects at risk of renal function decline and arterial stiffening.